DATA FIELD RICHARD C. MARTIN DALAM PENDEKATAN STUDI ISLAM - Mohammad Hotibul Umam; M. Lutfi Mustofa (Qolamuna : Jurnal Studi Islam, 2022)
This study focuses on mapping the approach to Islamic studies in one of Richar C. Martin's edited works entitled Approach to Islam in Religious Studies. This research takes a descriptive-analytical form which begins by revealing the writing background and approach in religious studies. Through this research, several conclusions can be drawn regarding Martin's academic anxiety, which he admits is the cause of the weakness between the theological approach that maintains a normative understanding of religion and the historical point of view of religion. Starting from this, then Richar C. Martin tried to bridge the gap by publishing a book which was the result of the edits of several essays or articles from outsiders and insiders who discussed the themes of Islamic studies and various approaches in Islamic studies. From this background, the purpose of this study is to focus on describing the approach to Islamic studies and describing the methodological approach to Islamic studies in religious studies in Richard C. Martin's Approach to Islam in Religious Studies. Key Word : Approach, Islamic Studies, Richard C. Martin